'Patient-Centered Care' for Complex Patients with Type 2 Diabetes Mellitus–-Analysis of Two Cases. (January 2013) - Hackel, Jennifer M.
Purpose: This paper serves to apply and compare aspects of person centered care and recent consensus guidelines to two cases of older adults with poorly controlled diabetes in the context of relatively similar multimorbidity. Methods: After review of the literature regarding the shift from guidelines promoting tight control in diabetes management to individualized person centered care, as well as newer treatment approaches emerging in diabetes care, the newer guidelines and potential treatment approaches are applied to the cases. Results: By delving into the clinical, behavioral, social, cultural and economic aspects of the two cases in applying the new guidelines, divergent care goals are reached for the cases. Conclusions: Primary care practitioners must be vigilant in providing individualized diabetes treatment where multiple chronic illnesses increase the complexity of care. While two older adults with multimorbidity may appear at first to have similar care goals, their unique preferences and support systems, as well as their risks and benefits from tight control, must be carefully weighed in formulating the best approach. Newer pharmaceutical agents hold promise for improving the possibilities for better glycemic control with less self-care burden and risk of hypoglycemia.